2013
DOI: 10.1002/eat.22140
|View full text |Cite
|
Sign up to set email alerts
|

Measured physical activity in anorexia nervosa: Features and treatment outcome

Abstract: PA is higher in patients with anorexia nervosa than age-matched controls both before and after treatment, and is associated with treatment dropout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 10 publications
4
72
4
2
Order By: Relevance
“…Cognitive impairments restrict the feasibility of self-reports [24] , particularly complex or lengthy questionnaires [102] , but the IPAQ has been validated for participants with severe mental illness [109110] . Furthermore, specific psychiatric conditions are associated with varying frequency of PA; for example, lower PA can be associated with anxiety and depression, while greater PA can be associated with eating disorders and alcohol abuse [109, 111] . As noted above, different levels of habitual PA intensity merit different measures.…”
Section: Choosing a Measure Of Pamentioning
confidence: 99%
“…Cognitive impairments restrict the feasibility of self-reports [24] , particularly complex or lengthy questionnaires [102] , but the IPAQ has been validated for participants with severe mental illness [109110] . Furthermore, specific psychiatric conditions are associated with varying frequency of PA; for example, lower PA can be associated with anxiety and depression, while greater PA can be associated with eating disorders and alcohol abuse [109, 111] . As noted above, different levels of habitual PA intensity merit different measures.…”
Section: Choosing a Measure Of Pamentioning
confidence: 99%
“…These activities are receiving greater attention in the study of AN, as little is known about their role in weight regulation, metabolism, and psychopathology. While patients with AN have been found to spend more time on their feet after treatment, and take more steps per day than healthy controls, (El Ghoch et al, 2013; Gianini et al, 2016) clinical understanding of fidgeting is less clear. Clinicians often report elevated levels of this behavior among patients, although objective assessment using a 5-site, wire-based activity monitorhas found no significant difference in fidgeting between patients and HCs (Gianini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates range between 34 and 55% (Dalle Grave et al, 2008; Bewell-Weiss and Carter, 2010; Sauchelli et al, 2015), and it has been associated with poorer treatment outcome (Shroff et al, 2006; Dalle Grave et al, 2008; Stiles-Shields et al, 2015), an increased likelihood of dropout during treatment (El Ghoch et al, 2013) and a shorter time to relapse (Strober et al, 1997; Carter et al, 2004). However, some studies have not found an association between exercise and treatment response (van Elburg et al, 2007; Kostrzewa et al, 2013), and there is evidence suggesting that supervised physical activity may be somewhat beneficial for outcome and attitudes toward exercise (Calogero and Pedrotty, 2004; Sauchelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%